Movement and Learning in the Early Years : Supporting Dyspraxia (DCD) and Other Difficulties - MacIntyre, Christine (SAGE Publications, Paul Chapman Publishing, 2004)
`This book achieves what it sets out to do - provide clear guidance to parents and professionals on key aspects of movement in the early years. The book however does more than that - it emphasises that movement in the early years is not the territory of experts, but through the use of this book, the assessment of movement development of activities and programmes are within the range of all - class teachers and parents. I strongly recommend that this book is available in every school' - Educational Review `This book provides a good overview of issues in movement and development and learning, and will stimulate the interested reader to explore this topic further' - Early Years `This book will be a useful addition to any primary staff room bookshelf. It is a practical book based on sound theory. It will provide ideas for the non-specialist teacher and for parents anxious to help. The suggestions will provide a good framework for the staged assessment and support for young children for whom there is a cause for concern' - Support for Learning `For anyone involved in the development of any young child, this should be essential reading. The book is very informative and readable by parents, teachers and students and is simply illustrated with case studies' - Dyslexia Contact `As a behaviour advisory teacher I will certainly be influenced by reading this, and I know our local occupational therapists would be overjoyed if she knew all teachers read books like this' - Special Children `It is always good to be able to welcome a book on such a key factor as movement in early childhood development, and this text has been written to support parents and practitioners who wish to understand how movement contributes to all aspects of learning -intellectual, social and emotional, as well as physical' - Marian Whitehead, Nursery World `This book is an excellent introduction for anybody trying to understand how movement affects child development. It clearly explains the importance movement has on how young children learn and feel. The information and insights in this book can be found elsewhere but I have yet to find such breadth and depth of information on supporting children with movement difficulties as clearly written and accessible as this book' - Spare-Chair `The book is very informative and readable by parents, teachers and students and amply illustrated with case studies' - Judith Stansfield, SEN ICT Consultant Movement is a key factor in young children's development and it can affect how they learn and how they feel. Do you work with young children who have difficulties in this area? This book shows you how to observe a child as they move to allow for early identification of any problem and then tells you how to help. Dyspraxia (DCD) is on the increase in young children and less confident and easy movement can play a part in other specific learning difficulties such as dyslexia, attention deficit disorder (ADD) and with hyperactivity (ADHD). Included is advice on: } observing, analyzing and assessing movement development } building confidence } helping with handwriting } supporting mathematical development Why not ask the child to pop bubble paper as one way of promoting finger awareness? Carefully taught activities can be easy to plan and fun to carry out and there are lots of suggested activities set out in the book. Early years practitioners in nurseries, schools, playgroups and EYDCPs will find this book clear and useful; it also offers advice to parents. Christine Macintyre was formerly Senior Lecturer at Edinburgh University and is now a freelance consultant. Kim McVitty is a nursery school teacher.